Constructing Artificial SEI Layer on Lithiophilic MXene Surface for High‐Performance Lithium Metal Anodes. Issue 6 (6th January 2022) - Zhao, Feifei; Zhai, Pengbo; Wei, Yi; Yang, Zhilin; Chen, Qian; Zuo, Jinghan; Gu, Xiaokang; Gong, Yongji
Abstract: MXene has been found as a good host for lithium (Li) metal anodes because of its high specific surface area, lithiophilicity, good stability with lithium, and the in situ formed LiF protective layer. However, the formation of Li dendrites and dead Li is inevitable during long‐term cycle due to the lack of protection at the Li/electrolyte interface. Herein, a stable artificial solid electrolyte interface (SEI) is constructed on the MXene surface by using insulating g‐C3 N4 layer to regulate homogeneous Li plating/stripping. The 2D/2D MXene/g‐C3 N4 composite nanosheets can not only guarantee sufficient lithiophilic sites, but also protect the Li metal from continuous corrosion by electrolytes. Thus, the Ti3 C2 T x /g‐C3 N4 electrode enables conformal Li deposition, enhanced average Coulombic efficiency (CE) of 98.4%, and longer cycle lifespan over 400 cycles with an areal capacity of 1.0 mAh cm −2 at 0.5 mA cm −2 . Full cells paired with LiFePO4 (LFP) cathode also achieve enhanced rate capacity and cycling stability with higher capacity retention of 85.5% after 320 cycles at 0.5C. The advantages of the 2D/2D lithiophilic layer/artificial SEI layer heterostructures provide important insights into the design strategies for high‐performance and stable Li metal batteries. Abstract : A stable artificial solid electrolyte interface is constructed on the MXene surface by using insulating g‐C3 N4 layer to regulate homogeneous Li plating/stripping. The amorphous g‐C3 N4 enables highly uniform artificial SEI and MXene provides sufficient lithiophilic sites for Li nucleation. The obtained Ti3 C2 T x /g‐C3 N4 composite electrode enables conformal Li deposition, enhanced average Coulombic efficiency, and longer cycle lifespan.